Markers of Memory CD8 T Cells Depicting the Effect of the BNT162b2 mRNA COVID-19 Vaccine in Japan - Kondo, Hiroyuki; Kageyama, Takahiro; Tanaka, Shigeru; Otsuka, Kunihiro; Tsukumo, Shin-ichi; Mashimo, Yoichi; Onouchi, Yoshihiro; Nakajima, Hiroshi; Yasutomo, Koji (Frontiers in Immunology, 2022)
BNT162b2, a nucleoside-modified mRNA vaccine for SARS-CoV-2 spike glycoprotein (S), provides approximately 95% efficacy for preventing COVID-19. However, it remains unclear how effectively memory CD8+ T cells are generated and which genetic and environmental factors affect the generation and function of memory CD8+ T cells elicited by this vaccine. Here, we investigated the frequency and functions of memory CD8+ T cells 3 weeks after the second vaccination in the Japanese population. Using a peptide-MHC pentamer, we detected an increased number of memory CD8+ T cells together with increased serum anti-S protein antibody in females compared with that in males, but the frequency of pentamer-positive cells was not positively correlated with antibody titers. Memory precursor effector cells (KLRG1-CD127+) among both CD8+ cells and pentamer+ cells and effector cells (CD38-HLA-DR+) among pentamer+ cells were more abundant in females than in males. Upon S protein-mediated stimulation of T cells, the intensity of CD107a and granzyme B expression was increased in females compared with that in males, indicating stronger memory CD8+ T cell responses in females than in males. Our studies showed that the BNT162b2 vaccine elicits increased memory CD8+ T cell proliferation and secondary CTL responses in females compared with those in males in the Japanese population. These findings provide an important basis for the distinct sex difference in cellular immune responses to mRNA vaccination and suggest that memory precursor effector cells can be one of markers to evaluate and boost cellular immunity induced by BNT162b2.